PENGARUH KEUNGGULAN DAN KETERBATASAN PERUSAHAAN TERHADAP KESEMPATAN BERTUMBUH PERUSAHAAN (GROWH OPPORTUNITIES) - Murni, Rochiyati Murni; Mulyasari, Windu Mulyasari (Universitas Muhammadiyah Magelang, 2004)
This paper examined the relationship between the model growth opportunities rests on combining the firm advantages and liminatons, and the investment opportunity sets. This research, particularly, extend the work of AINajjar and Belkaoui (2001) for Indonesian conditions. I used financial institutions as the sample of my research. This research aimed to examined the growth opportunities of financial institutions because this sector in last several yaer in very bad conditions. The conditions happened because of economic consequence also there is a merger between banks. The firm advantages are used four variables such corporate reputation, multinational, size and profitability. Two variables are used as firm limitations such leverage and systematic risk. This research find evidence that profitability as firm advantages and laverage as firm limitation confirmed with the general model of growth opportunities. Nevertheless, the relationship between leverage and IOS are directly related, where this relation are not consistent with the theory.